Legal Aliens: Experiencing Civic Marginalisation in Entrepreneurship in South Africa - Nyakabawu, Shingirai (Frontiers in Human Dynamics, 2022)
This study focuses on challenges faced by Zimbabwean migrant entrepreneurs in South Africa involved in agro processing, transport and logistics, information technology, transport, education, accounting, remittances among others. These challenges stem from the limits of temporary residence permits. These include delays in adjudication of residence permits renewals which threaten the viability of migrant owned businesses, access to finance, conditions of the temporary protected statuses of Zimbabwean permits xenophobia and their experience with affirmative action laws. Based on data gathered through interviews in Cape Town, this study concludes that migrant entrepreneurs remain in positions of vulnerability and contribute disproportionately to the economy of South Africa because of limitation of residence visas.